Winning on our Issues with Power - Amanda Tattersall (Cosmopolitan Civil Societies: An Interdisciplinary Journal, 2009)
Social movement organisations need to have a pragmatic understanding of our current weaknesses and challenge ourselves to be much more adventurous for how to build social power and transformative change. This article considers three core weaknesses of our activist organisations, including how our issue agenda is often reactive, our disconnection from place and our poor track record on collaboration. It then suggests that the hope for stronger social change lies with a proactive issue agenda, strong reciprocal coalitions and the ability to move campaigns at multiple scales (locally, regionally, nationally, globally). The article includes a variety of examples that suggest how this stronger kind of organising is possible.